Critical Review—Water-Soluble Near-Infrared Fluorophores Emitting over 1000 nm and Their Application to In Vivo Imaging in the Second Optical Window (1000–1400 nm). (1st January 2018) - Tsuboi, Setsuko; Yamada, Sayumi; Nakane, Yuko; Sakata, Takao; Yasuda, Hidehiro; Jin, Takashi
Abstract : Near-infrared (NIR) emitting fluorophores are widely used as bio-imaging probes for non-invasive visualization of deep-tissues at the whole body level, because of the high permeability and low absorption of NIR light in living tissues. Recently much attention has been paid for NIR fluorescence imaging at the wavelengths of 1000–1400 nm (second optical window) to obtain clearer deep-tissue images with high signal to background ratios. This is because that the NIR light with longer wavelengths (1000–1400 nm) is highly permeable with lower scattering compared with the conventional NIR light (700–1000 nm). In the second optical window, there are a very limited number of fluorophores that can be used for NIR fluorescence imaging. To date, single walled carbon nanotubes (SWNTs), PbS quantum dots (QDs) and Ag2 S QDs, rare-earth metal doped nanoparticles (NPs) have been reported as NIR fluorophores for in vivo imaging in the second optical window. In this work, we synthesized several types of water-soluble NIR fluorophores, glutathione coated PbS QDs, glutathione coated Ag2 S QDs Er 3+ -doped NaYF4 nanoparticles (Er 3+ -NPs) and cholate-capped SWNTs that emit over 1000 nm. For the application of the NIR fluorophores to in vivo imaging, we examined their fluorescence brightness, particle size, and cytotoxicity. We found that among the NIR fluorophores, PbS QDs are the brightest fluorophore (quantum yield, 4%) with no significant cytotoxicity. The fluorescence of Ag2 S QDs, Er 3+ -NPs, and SWNTs was at least 50 times week compared with that of PbS QDs. We show the capability of the NIR fluorophores for in vivo imaging of cerebral blood vessels, tumor angiogenesis, lymph nodes, and phagocytic cell migration in mice.